Temperature, climate change, and human conception rates: Evidence from Hungary - Tamás Hajdu; Gábor Hajdu (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
In this paper, we examine the relationship between temperature and human conception rates and project the impacts of climate change by the mid-twenty-first century. Using complete administrative data on 6.8 million pregnancies between 1980 and 2015 in Hungary, we show that exposure to hot temperatures reduces the conception rate in the first few weeks following the exposure, but a partial rebound is observed after that. Absent adaptation, climate change is projected to increase seasonal differences in conception rates, and a decline is expected in terms of annual conception rates. This latter decline is driven by a change in the number of induced abortions and spontaneous fetal losses. The overall number of live births is unaffected. However, some newborns may experience non-negligible consequences because of the altering in utero temperature exposure due to a shift in the timing of conception.
Keywords: J13; Q54; 330; conception rate; fertility; temperature; weather; climate change